2013
DOI: 10.1158/1078-0432.ccr-12-2978
|View full text |Cite
|
Sign up to set email alerts
|

The Tumor-Suppressive Function ofUNC5Dand Its Repressed Expression in Renal Cell Carcinoma

Abstract: Purpose: As a newly added member of the UNC5H receptors, the function of UNC5D/H4 in tumorigenesis remains poorly defined. The aim of this study was to examine the expression of UNC5D in primary renal cell carcinomas (RCC), analyze the mechanisms responsible for its downregulation in RCC, and assess its functional relevance to tumor growth and migration.Experimental Design: Forty-four paired primary RCCs and corresponding adjacent noncancerous tissues were collected. The mRNA and protein expression level of UN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 45 publications
(44 reference statements)
3
20
0
Order By: Relevance
“…The two cell lines resulted in the formation of tumors of different sizes on the back of mice and lethality at 32 days to 47 days after injection. UNC5D overexpression has been suggested to inhibit cell multiplication, migration and invasion in renal cancer cells by inducing cell cycle arrest at G2/M phase [12]. These data indicated that UNC5D may act as a tumor suppressor and are consistent with our findings in bladder cancer cells.…”
Section: Resultssupporting
confidence: 91%
“…The two cell lines resulted in the formation of tumors of different sizes on the back of mice and lethality at 32 days to 47 days after injection. UNC5D overexpression has been suggested to inhibit cell multiplication, migration and invasion in renal cancer cells by inducing cell cycle arrest at G2/M phase [12]. These data indicated that UNC5D may act as a tumor suppressor and are consistent with our findings in bladder cancer cells.…”
Section: Resultssupporting
confidence: 91%
“…Epigenetic changes are common features of PCa, and play key roles in the initiation and progression of cancer . As for UNC5D , hypermethylation alterations at the promoter region are one of the main causes for its repression in a variety of tumors, and are the same in PCa cells according to our study. However, there are seldom reports on the methylation status of UNC5D in metastatic tumors.…”
Section: Discussionsupporting
confidence: 60%
“…Adenoviruses expressing UNC5D , UNC5D‐∆DD (UNC5D without the death domain), or MOCK were packaged by the Vector Gene Technology Company (Beijing, China). Prostate cancer cell lines were infected with 20 MOI of the adenoviral vector.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations